From data to levy design. The five stages of implementing housing taxes - Erling Røed Larsen (Statistics Norway, Research Department, 2009)
Taxes on housing consumption have attractive features. They can enhance overall efficiency, function as automatic stabilizers, and work progressively. Implementation, however, requires a careful balance between economic ambition and political reality. This article suggests a 5-stage procedure: identification; estimation; data acquisition and combination; empirical investigation; and tax function construction. It illustrates how to implement by employing the rental-equivalence principle to estimate recent values of owner-occupied housing consumption in a cross-section of Norwegian households by imputing rent for owners based on observed rents in rental markets. It analyzes the distribution of imputed rent over the income range, and demonstrates that imputed rent is a necessary good. A simple tax scheme on real households in a dataset from 2006, shows how a housing tax can be structured with attractive features. Such a tax scheme would, in contrast to the current interest payment subsidy, work counter-cyclically and could, if used as a substitute for income taxes, reduce deadweight losses from labor income taxes. In its suggested form, it would generate approximately 12 billion NOK in revenue for Norway.
Keywords: C14; C21; D12; D63; H23; 330; automatic stabilization; deadweight loss; distribution; efficiency; housing taxation; imputed rent; progressive levy; rental equivalence